The Influence Of Public Accountability, Transparency, And Integrity On The Quality Of Perumnas Financial Reports In North Sumatra - Panjaitan, Renaldi; Sucipto, Tia Novira; Wardhani, Neng Sri (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2026)
This study aims to empirically examine the influence of public accountability, transparency, and integrity on the quality of financial statements at Perum Perumnas of North Sumatra. The research specifically investigates the partial and simultaneous effects of each variable on improving financial reporting quality and identifies the most dominant contributing factor. A quantitative approach with an explanatory research design was employed using a survey method. The study sample consisted of 37 employees directly involved in the management and preparation of financial statements, selected through a convenience sampling technique. Data were collected using structured questionnaires measured on a five-point Likert scale and analyzed using multiple linear regression with the assistance of SPSS software. The findings reveal that public accountability, transparency, and integrity have a positive and significant effect on the quality of financial statements, both individually and simultaneously. Among these variables, integrity emerges as the most dominant factor influencing financial reporting quality. These results highlight the importance of implementing good governance principles to enhance financial reporting practices. The study concludes that strengthening accountability, information transparency, and personnel integrity is essential for improving the quality of financial statements in State-Owned Enterprises, particularly within Indonesia’s housing sector.